Comparison of a Novel Muscle Training Device with Conventional Rehabilitation Training in Motor Dysfunction of Lower Limb Patients: A Pilot Study - Cai XY (Dove Medical Press, 2020)
Xin-ying Cai,1 Dong-qi Lin,2 Zhi-zhen Xiao,3 Dan-dan Zhang,3 Ying Lin,3 Han-yu Chen,4 Yan-xing Xu,3 Yu-hua Zhou3 1Clinical Medical Research Center, Shantou Central Hospital, Affiliated Shantou Hospital of Sun Yat-Sen University, Shantou, Guangdong, People’s Republic of China; 2Department of Cardiothoracic Surgery, The Second Affiliated Hospital of Shantou University Medical College, Shantou, Guangdong, People’s Republic of China; 3Nursing Department, Shantou Central Hospital, Affiliated Shantou Hospital of Sun Yat-Sen University, Shantou, Guangdong, People’s Republic of China; 4Rehabilitation Department, Shantou Central Hospital, Affiliated Shantou Hospital of Sun Yat-Sen University, Shantou, Guangdong, People’s Republic of ChinaCorrespondence: Yu-hua ZhouNursing Department, Shantou Central Hospital, Wai-ma Road 114, Shantou City, Guangdong Province, People’s Republic of ChinaTel +86 0754-88903584Fax +86 0754-88548117Email zhouyuhua1023@163.comDong-qi LinDepartment of Cardiothoracic Surgery, The Second Affiliated Hospital of Shantou University Medical College, Shantou, Guangdong, People’s Republic of ChinaTel +86 0754-88915647Email doctorldq@163.comBackground: Postoperative functional training for fracture or osteoarthritis is mainly focused on functional self-exercise, which aims to recover the function of the lower limbs.Purpose: To compare the function and life quality recovery in patients with fracture or arthritis treated with novel muscle training device (NMT) or conventional rehabilitation training (CRT) following surgery.Patients and Methods: A total of 32 fracture patients were randomly divided into the NMT or the CRT groups. The evaluation was performed on the first and 7th day after surgery. The outcome measurements included the incidence of foot drop, Deep Vein Thrombosis and pressure ulcers, Hospital for Special Surgery knee score (HSS scores), pain scores for the Visual Analogue Scale (Pain scores for VAS), Zung self-rating anxiety scale (SAS), Pittsburgh sleep quality index (PSQI) and the Barthel Index score.Results: The comparison of the change scores between the two groups indicated significant differences on day 7 following surgery in the Barthel Index score (P< 0.01). The Pain scores for VAS between the two groups indicated a significant difference (P< 0.05, U=20.0). The HSS scores between the two groups indicated a significant difference (P< 0.05, U=19.0). The HSS scores exhibited a highly significant difference in the NMT group (P< 0.01). The Mann–Whitney test was used to analyze the various components of the HSS scores. The comparison of the change scores on the function between the two groups indicated a significant difference (P< 0.05). The Range of Motion difference between groups exhibited highly significant differences (P< 0.01).Conclusion: The novel muscle training device positively influenced the decrease in pain score, which resulted in a range increase of knee joint movement and a significant overall improvement in motion.Keywords: orthopedics, fracture, middle-aged and elderly, function exercise